DEVELOPMENT OF NUMERACY-BASED MATHEMATICS LEARNING MODULES ON FLAT SIDE SPACE BUILDING MATERIALS - Cahyani, Putri; Kurniawati, Naning; Ismanto, Ismanto (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
The numeracy abilities of some students in class VIII SMP Plus Al Fatimah are still relatively low so special measures are needed, accompanied by ineffective teaching materials because there are too few material descriptions and the learning methods used are still conventional. So, it is necessary to develop teaching materials in the form of numeracy-based mathematics learning modules as a companion to the textbooks provided by the school. The research aims to develop a mathematics module on flat-sided geometric material that is valid and practical. The type of research used is Research and Development (R & D) with the ADDIE development method (analysis, design, development, implementation, and evaluation). The results of the development research obtained a numeration-based mathematics learning module on flat-sided geometric material with valid and practical categories. The learning module was declared valid by the validator, media experts scored 72.5% in the "valid" category and material experts scored 82.6% in the "very valid" category, the average score was 77.9% in the "valid" category. For the results of the student trials, the practical aspect obtained an average score of 83.195% in the "very practical" category. It can be concluded that the learning module that has been developed is suitable for use.